2019
DOI: 10.1111/cns.13254
|View full text |Cite
|
Sign up to set email alerts
|

High expression of COPB2 predicts adverse outcomes: A potential therapeutic target for glioma

Abstract: Aims To evaluate the clinical significance of coatomer protein complex subunit beta 2 (COPB2) in patients with glioma using a bioinformatics analysis. Methods Oncomine, GEO, and The Cancer Genome Atlas databases were used to examine the COPB2 transcript levels in glioma tissues. Gene expression profiles with clinical information from low‐grade glioma and glioblastoma (GBM) projects were analyzed for associations between COPB2 expression and clinicopathologic characteristics. Kaplan‐Meier survival and Cox regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…To clarify THBS1-related immunologic biological processes in GBM, 7 inflammatory metagene signatures were selected based on previous studies to explore their association with THBS1 in the TCGA-GBM dataset ( 26 28 ). The results indicated that THBS1 was positively correlated with most immune signatures (HCK, MHC-I, MHC-II, STAT1, interferon, LCK and IgG) and negatively correlated with KIRK1, IGSF1, IFI44L and IFIT1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To clarify THBS1-related immunologic biological processes in GBM, 7 inflammatory metagene signatures were selected based on previous studies to explore their association with THBS1 in the TCGA-GBM dataset ( 26 28 ). The results indicated that THBS1 was positively correlated with most immune signatures (HCK, MHC-I, MHC-II, STAT1, interferon, LCK and IgG) and negatively correlated with KIRK1, IGSF1, IFI44L and IFIT1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…7; GraphPad Software, Inc.) was used to compare THBS1 expression between different groups. Gene expression heatmaps of the association between THBS1 and inflammatory metagene clusters, Treg signatures (26)(27)(28) and THBS1-correlated genes were generated using ClustVis (http://biit.cs.ut.ee/clustvis/; first version online; date accessed 2014-10-31) (7). The Tumor IMmune Estimation Resource database (TIMER; cistrome.shinyapps.io/timer) was used to estimate the abundance of immune infiltrates (29).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the functions of COPB2 in tumors have been increasingly studied. In gliomas, COPB2 has been reported to be an important factor in the regulation of the immune microenvironment, and its high expression is related to adverse outcomes [ 14 ]. In breast cancer, COPB2 may predict metastasis [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the main functions of COPB2 are the regulation of extracellular membrane transport and mediation of retrograde transport from the Golgi complex to the endoplasmic reticulum (ER) [11][12][13]. Recently, COPB2 was reported to have important correlations with various cancer types and has different functions in different tumors, such as breast cancer, glioma, and prostate cancer [14][15][16]. Silencing COPB2 can inhibit the proliferation of colon cancer cells by inducing cell cycle arrest [17].…”
Section: Introductionmentioning
confidence: 99%
“…Mi Y et al have reported that COPB2 is highly expressed in human prostate cancer and promoted the proliferation of prostate cancer cells [24]. Many studies have found that COPB2 was up-regulated in various human tumors, such as breast cancer, gastric cancer [46] and glioma [47]. Is COPB2 also related to the occurrence and development of colorectal cancer?…”
Section: Plos Onementioning
confidence: 99%